2021
DOI: 10.1007/s40415-020-00691-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of three CoIDA genes in Camellia oleifera

Abstract: The INFLORESCENCE DEFICIENT IN ABSCISSION (IDA) controls floral organ abscission in plants. IDA belongs to IDA-LIKE (IDL) gene family that is involved in regulation of Arabidopsis development. Herein, we identified three genes, CoIDA1, CoIDA2 and CoIDA3 in Camellia oleifera (Camellia oleifera Abel. cv. Huashuo) and suggested their involvement in the regulation of fruits abscission. The full-length cDNA sequences of CoIDA1, CoIDA2 and CoIDA3 were of 207 bp, 276 bp and 273 bp, encoding proteins of 68, 91 and 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In mango, after ethylene induction, the expression of MiIDA1 and MiIDA2 had upregulated and the formation of the abscission layer was promoted (Rai et al, 2021). In Camellia oleifera, CoIDAs are abscission-associated genes, which can be induced by ethylene and push forward the formation of the abscission layer (Yang et al, 2021). Our previous studies have shown that ethylene treatment stimulates the formation of the abscission layer in cotton, and the genome-wide analysis showed that it was related to miRNA (Guo et al, 2018).…”
Section: Formation Of the Abscission Layer Of The Cotton Boll Stalk I...mentioning
confidence: 99%
“…In mango, after ethylene induction, the expression of MiIDA1 and MiIDA2 had upregulated and the formation of the abscission layer was promoted (Rai et al, 2021). In Camellia oleifera, CoIDAs are abscission-associated genes, which can be induced by ethylene and push forward the formation of the abscission layer (Yang et al, 2021). Our previous studies have shown that ethylene treatment stimulates the formation of the abscission layer in cotton, and the genome-wide analysis showed that it was related to miRNA (Guo et al, 2018).…”
Section: Formation Of the Abscission Layer Of The Cotton Boll Stalk I...mentioning
confidence: 99%
“…Ethylene is an essential hormone in plants, which plays an momentous role in the whole process of plant growth and development [25] .At the same time, ethylene can also induce the formation of abscission zone and cause the abscission of owers and fruits.In mango,after ethylene induction,MiIDA1 and MiIDA2 expression had upregulated,then promoted the formation of abscission zone [26] . In Camellia oleifera,CoIDAs are abscission associated genes which can be induced by ethphon and push forward the formation of abscission zone [27] .Our previous studies have shown that ethephon treatment simulates abscission layer formation in cotton,and Genome-wide analysis showed that it was related to miRNA [28] . In this experiment, cotton boll stalk abscission zone was treated with 200 mg• L − 1 , 400 mg•L − 1 and 800 mg•L − 1 ethrel, and abscission layer was found after 24 hours, which indicated that the abscission layer of cotton boll stalk could be induced by ethrel above 200 mg•L − 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Ethylene is an important phytohormone regulating the fruit abscission of oiltea-camellia. In the abscission zone of abnormal fruits, the 1aminocyclopropane-1-carboxylic acid (ACC) content increased significantly (Hu et al, 2021). The expressions of genes CoACO1 and CoACO2 increased significantly in the abscission zone of abnormal fruits (Hu et al, 2021).…”
Section: Fruit Abscission and Fruit Sizementioning
confidence: 99%
“…In the abscission zone of abnormal fruits, the 1aminocyclopropane-1-carboxylic acid (ACC) content increased significantly (Hu et al, 2021). The expressions of genes CoACO1 and CoACO2 increased significantly in the abscission zone of abnormal fruits (Hu et al, 2021). These genes were critical in ethylene regulation.…”
Section: Fruit Abscission and Fruit Sizementioning
confidence: 99%
See 1 more Smart Citation